ANALISIS VALIDITAS TERHADAP PENGEMBANGAN PENUNTUN PRAKTIKUM IPA BERBASIS MODEL PEMBELAJARAN COLLABORATIVE TEAMWORK LEARNING (CTL) UNTUK SISWA SMPN SE KECAMATAN BONJOL KABUPATEN PASAMAN: (Analysis of the validity of the Development of Scientific Practicum Developers Based on Collaborative Teamwork Learning (CTL) Learning Models for Students SMPN, Bonjol Sub District, Pasaman District) - Ennike Gusti Rahmi; Rini Silvina (Perspektif Pendidikan dan Keguruan, 2019)
Teachers carry out practical activities not yet using practicum guides. Practical activities carried out by teachers have tended to only provide instruction. This is because the school does not yet have a practical guidebook. Difficulties are also faced by students, because students do not know what practical activities will be carried out and cause a lack of preparation of students in practicing. This study aims to produce a practical guide based on Collaborative Teamwork Learning on life organization system material for class VII students in SMP in Bonjol Subdistrict, Pasaman Regency, which is valid. The type of development research (Develpomental research), the development model in the form of a descriptive procedural model which outlines the steps that must be followed to produce the product. The data collection technique used was a validation sheet questionnaire. The validity of the Collaborative Teamwork Learning practicum test conducted by material experts and media experts from the validation results obtained a percentage value based on aspects of didactic requirements 83.33%, aspects of construct requirements 84.72%, aspects of technical requirements 82.29% and aspects of language requirements is 89.58%. The overall validity test results obtained a percentage value of 84.98% with valid criteria. based on the results of the validity test the practicum guide analysis developed was valid for use in practical activities.